Financial Crisis, Environmental Turbulence and International Trade. The Case of Italy - Maria Garbelli (European Scientific Journal, ESJ, 2018)
In 2007 United States of America gave birth to a global, deep and disruptive phenomenon, well known as Financial Crisis. Despite the specific overseas location it first appears, the global crisis comes very fast in Europe, affecting several Countries in different ways and threating both Government and the economic tissue of the Nations. Since the crisis first appears, Italy has faced the global economies collapse: trade inside and outside the Nation felt down, with a loss of competitiveness of the Country compared to other EU’: lower earns and the credit crunch implicate a raise of failures cases, and a competitive position loss in several industries. Almost ten years after the crisis very begin, and using Italian data, the paper give a measure of the crisis impact on international trade geography for the Country.